Interplay of dynamical and explicit chiral symmetry breaking effects on a quark - Serna, Fernando E. [UNESP]; Chen, Chen [UNESP]; El-Bennich, Bruno [UNESP] (Amer Physical Soc, 2019)
The relative contributions of explicit and dynamical chiral symmetry breaking in QCD models of the quark-gap equation are studied in dependence of frequently employed Ansatze for the dressed interaction and quark-gluon vertex. The explicit symmetry breaking contributions are defined by a constituent-quark sigma term whereas the combined effects of explicit and dynamical symmetry breaking are described by a Euclidean constituent-mass solution. We extend this study of the gap equation to a quark-gluon vertex beyond the Abelian approximation complemented with numerical gluon- and ghost-dressing functions from lattice QCD. We find that the ratio of the sigma term over the Euclidean mass is largely independent of nonperturbative interaction and vertex models for current-quark masses, m(u,d)(mu) <= m(mu) <= m(b)(mu), and equal contributions of explicit and dynamical chiral symmetry breaking occur at m(mu) approximate to 400 MeV. For massive solutions of the gap equation with lattice propagators this value decreases to about 200 MeV.